Drought impacts on livestock and crop production along an urban-rural gradient: perceptions and response strategies in the Eastern Cape province, South Africa - Pamla, Avela (Rhodes University, Faculty of Science, Department of Environmental Science)
Drought is a major challenge threatening agricultural productivity in urban and rural areas across southern Africa. Drought events are expected to be more frequent, severe, last longer, and, impact land-based livelihoods in the coming decades. Despite the growing literature on the impacts of drought on livelihoods, there is limited focus on the impacts of droughts across rural-urban gradients. The study examined small-scale farmers' perceptions of drought impacts and response strategies in the contexts of persistent droughts in the Eastern Cape province of South Africa. A total of 163 respondents, practicing livestock and/or crop farming across six towns, in urban and rural contexts were purposively identified. The study used snowball sampling approach to identify the relevant respondents. Data were collected through a semi-structured questionnaire survey, exploring the respondents' socio-demographic profiles, agricultural activities, perceptions of drought impacts, and drought response strategies. Qualitative data were coded and analyzed using descriptive statistics, thematic analysis, t-tests, and chi-square tests to identify patterns, themes, and relationships within the data. Nearly all (>95%) respondents owned livestock while substantially more rural farmers (81%) than urban farmers (35%) engaged in crop production. Drought was perceived by a sizeable proportion (>70%) of small-scale farmers as a very serious environmental challenge with adverse socio-economic repercussions on land-based activities. Livestock losses and crop failure were the key impacts reported by small-scale farmers in both rural and urban settings. About 86% of respondents across the sample reported declines in crop yields, with significantly more farmers in rural sites (45%) than urban sites (31%) reporting so. A substantial proportion of farmers across the sample (93%) reported drought response strategies relating to livestock and crop production, such as changing of farming practices, use of drought-resistant crops and government support, with slight differences in the proportion of farmers reporting so between urban (89 %) and rural (95 %) sites. Concerning government support, most respondents (>70%) stated that they were dissatisfied, with slightly more respondents in urban areas (77%) than in rural (70%) areas reporting so. Overall, the results of this study suggest a minimal response capacity of small-scale farmers to droughts in both rural and urban settings due to socio-economic and administrative factors, which calls for the need for drought-response strategies to build adaptive capacity for small-scale farmers. Turning to close cooperation between different stakeholders, such as local farmers, government officials, practitioners, and scientists might allow co-production of knowledge needed to inform drought response strategies. In some instances, attention needs to be given to farmers who are more vulnerable than others.
Keywords: Livestock Effect of drought on -- South Africa -- Eastern Cape; Farms, Small -- South Africa -- Eastern Cape; Crops and climate -- South Africa -- Eastern Cape; Drought management -- South Africa -- Eastern Cape